2020
DOI: 10.3390/insects11100717
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Cost of a Nutritional Symbiont Manifests in Delayed Reproduction in a Grain Pest Beetle

Abstract: Animals engage in a plethora of mutualistic interactions with microorganisms that can confer various benefits to their host but can also incur context-dependent costs. The sawtoothed grain beetle Oryzaephilus surinamensis harbors nutritional, intracellular Bacteroidetes bacteria that supplement precursors for the cuticle synthesis and thereby enhance desiccation resistance of its host. Experimental elimination of the symbiont impairs cuticle formation and reduces fitness under desiccation stress but does not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 54 publications
(80 reference statements)
2
22
2
Order By: Relevance
“…Concordantly, experimentally symbiont depleted (aposymbiotic) beetles exhibit a thinner and less melanised cuticle than their symbiotic counterparts (Hirota et al, 2017;Engl et al, 2018) and show a reduced resistance to desiccation and lower fitness under dry ambient conditions (Engl et al 2018). However, besides delayed reproductive maturation in symbiotic beetles, no further differences between symbiotic and aposymbiotic beetles regarding other life history traits were observed in laboratory rearing conditions (Engl et al, 2020).…”
Section: Journal Of Experimental Biology • Accepted Manuscriptmentioning
confidence: 98%
“…Concordantly, experimentally symbiont depleted (aposymbiotic) beetles exhibit a thinner and less melanised cuticle than their symbiotic counterparts (Hirota et al, 2017;Engl et al, 2018) and show a reduced resistance to desiccation and lower fitness under dry ambient conditions (Engl et al 2018). However, besides delayed reproductive maturation in symbiotic beetles, no further differences between symbiotic and aposymbiotic beetles regarding other life history traits were observed in laboratory rearing conditions (Engl et al, 2020).…”
Section: Journal Of Experimental Biology • Accepted Manuscriptmentioning
confidence: 98%
“…Measuring host fitness in the absence of symbionts is relatively straightforward, as aposymbiotic hosts can be reared by treating mothers with antibiotics. The results of these treatments clearly demonstrate that reproduction, development and immunity are severely compromised in the absence of symbionts [22,[74][75][76][77]. More challenging is manipulating symbiont density and measuring effects on host fitness.…”
Section: (D) Fitness Consequences Of Symbiont Density In Hosts: Empirical Constraints and Theoretical Insightsmentioning
confidence: 99%
“…As well as the benefits acquired by hosts of participating in mutualistic symbioses with bacteria, there are costs to hosts associated with providing the energy and nutrients to maintain a symbiont population (e.g. [ 22 ]). The net benefit to a host is therefore determined by the difference between the benefit and cost, with both benefits and costs potentially depending on the size of the symbiont population.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that symbiotic bacteria contribute to host variation, heat tolerance (Zhang, Leonard, et al., 2019 ), and temperature preference (Hague et al., 2020 ). Meanwhile the host should also bear the metabolic and fitness‐dependent cost to symbiont bacterial presence (Engl et al., 2020 ; Oliver et al., 2008 ); bacterial symbionts even can shape their host evolution (Coffman & Burke, 2020 ). Therefore, it is very important and necessary for insects to maintain a balanced population of symbiotic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile the host should also bear the metabolic and fitnessdependent cost to symbiont bacterial presence (Engl et al, 2020;Oliver et al, 2008); bacterial symbionts even can shape their host evolution (Coffman & Burke, 2020). Therefore, it is very important and necessary for insects to maintain a balanced population of symbiotic bacteria.…”
mentioning
confidence: 99%